Using digital repeat photography to strengthen seasonal monitoring in Ethiopia’s R4 Rural Resilience Initiative - Aredo, Samson Dejene; Kramer, Berber (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This paper discusses the feasibility of applying a near-surface remote sensing approach in the index insurance component of the R4 Rural Resilience Initiative in Ethiopia. Specifically, we test a prototype for using smartphone images of insured fields (or ‘picture-based insurance’) to monitor crops and manage basis risk in R4 insurance policies. We find that the proposed prototype, in which R4 agents send in images of crops grown by farmers in their communities, is feasible. Further, we find that crop losses are not only caused by droughts, which are covered by R4 index insurance products, but also by other perils such as pests or disease, which are not easily captured by index insurance. Despite limited smartphone penetration and current challenges in internet coverage, the near-surface remote sensing approach appears valuable and feasible in the context of the R4 Rural Resilience Initiative in Ethiopia.